PERLAKUAN AKUNTANSI TERHADAP DENDA KARTU KREDIT BANK SYARIAH PADA PT. BANK BNI SYARIAH CABANG SURABAYA - NUKE M, DEVIANITA Nuke (Jurnal Akuntansi AKUNESA, 2013)
In Indonesia there are two Islamic credit card, Dirham card first and thesecond is Hasanah BNI card. Issuance of Islamic credit cards is a new productthat is still many people who do not understand about this Islamic credit card.Here the authors chose to use the card as research hasanah to discuss about theaccounting treatment of credit card fine of Islamic banks. There are manydifferences between a conventional credit card and credit card syariah, frominterest and penalties provided. The result is derived from fines penalties due on aconventional credit card entry in the company's revenue, but the fines imposed onthe due date of payment on a credit card in the budget Islamic virtue or indonated funds, and fines are called ta'widh.keywords : credit card syariah and fine